Dos direitos trabalhistas para a vida profissional ao empoderamento das mulheres rurais - Engelmann, Paula Piccinin Paz (2023)
This dissertation analyzed the contribution of achievements within the scope of rural women's labor rights for the empowerment of women farmers from mothers' clubs in the municipality of Santa Helena-PR. In this context, with the expansion of labor rights, rural women are increasingly empowered, by expanding their freedom and their decision-making power in planning to solve problems within the rural property. Such conquests of the right to work for rural women, promote fundamental contributions to their empowerment, retirement, as well as to the rural development of the property. Several were the conquests of women, for example, in 1932 the right to vote, 1951 equal remuneration in the same function, 1988 the Federal Constitution extended several rights; 2001 creation of UN women. Despite all these achievements, there are still practical difficulties with these rights. The division of labor is part of history with justifications guided by biological issues, but female work still does not receive the due appreciation compared to the appreciation of male work, due to its historical culture. In this sense, the study was exploratory, with a cross-section in 2023, without considering the evolution of data over time. Primary source data were collected through questionnaires applied to 68 rural women, who were invited to participate spontaneously in the research, Peasants (15), Luzianas (13), Semper Alegre (40), Clubes de Mães in the municipality of Santa Helena-PR. In the first part, the profile of these rural women was raised through an interview, with varied scales, with 28 questions; the contribution of labor rights to your professional life with 16 questions and the contribution of labor rights to your empowerment with 16 questions. The scale used was: nothing contributes, contributes little, contributes and contributes a lot. Data were treated as percentages and analyzed descriptively. The results showed that labor rights added to professional life for 67%, as for labor rights for the empowerment of 60% of rural women. All indicators analyzed showed that yes, labor rights contributed to the personal empowerment of rural women, mainly in terms of respect for decisions, emotional support from other rural women and their families, decision-making, participating in discussions that take place in the community, financial right to land,house, car, profits and sales, personal empowerment, professional relationships, own income, valued for working outside the home, equality in work relationships with nine nominations, followed by respect or leadership, decision support, trust in myself and my opinions. However, for 22,33% of rural women, these rights did not contribute to their empowerment, especially in terms of standard of living and personal gain. This contribution needs to be expanded between the letter of the law and its compliance, which requires speed of public policies in effective compliance and agility of the laws in receiving these rights, since in the general evaluation the average contribution of the achievements for empowerment was 7.